Laparoscopic appendectomy to remove a metallic foreign body in a wild Bornean orangutan (Pongo pygmaeus) undergoing rehabilitation. Issue 6 (12th August 2016) - Llano Sanchez, Karmele; Handayani, Ayu B.; Nelson, Christine L.; Eng, Jaclyn W.L.; Prameswari, Wendi; Hicks, Nigel; Pizzi, Romain
Abstract: A laparoscopic appendectomy was performed in a wild orangutan ( Pongo pygmaeus ) undergoing rehabilitation, for a metal nail found on radiographs, using 3‐mm instrumentation. Post‐operative healing was rapid and uneventful, with return to the forest within 10 days. This is the first report of minimally invasive surgery in a wild orangutan.